Studi Deskriptif Riset Kebijakan Tentang Hak-Hak Difabel di Indonesia - Okki Ambarwati; Amalina Putri; Riant Nugroho (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2022)
The current paradigm regarding disability has evolved. Starting from the terminology of the difable that has evolved and the policies that govern it. Other developments are manifested by the growing community, institutions, study, policy research and other elements that are concerned with increasing the dignity of people with disabilities. The purpose of this research is to see trends in policy research as seen from policy research models and research themes based on the rights of people with disabilities as regulated in policies The Systematic Literature Review technique was used to collect literature related to disability policy research in Indonesia in the Scopus database. There were 36 articles relevant to research on disability policy in Indonesia. The results show that following Law Number 8 of 2016 concerning persons with disabilities influenced the development of disability policy research in Indonesia. The policy content research model and the policy environment are the most widely used models in research. Meanwhile, the most discussed theme trends are the right to education, the right to social welfare, the right to justice and legal protection, the right to disaster protection and the right to be free from stigma. Recommendations for further research are to look at research with policy implementation and evaluation models. Further practical implications are discussed in the article.